Altered expression of Transforming Growth Factor Beta isoforms in bovine cystic ovarian disease - Matiller, Valentina (2014)
Cystic ovarian disease (COD) is one of the main causes of infertility in dairy cattle. It has been shown that intra-ovarian factors may contribute to follicular persistence. Transforming growth factor-beta (TGFB) isoforms are important paracrine and autocrine signalling molecules that regulate ovarian follicle growth and physiology. Considering the importance of these factors in the ovarian physiology, in this study, we examined the expression of TGFB isoforms (TGFB1, TGFB2 and TGFB3) in the ovary of healthy cows and animals with spontaneous and adrenocorticotrophic hormone (ACTH)-induced COD. In the oestrous-synchronized control group, the expression of TGFB1 in granulosa and theca cells was higher in spontaneous cysts than in atretic or tertiary follicles. When we compared TGFB2 expression in granulosa cells from atretic or tertiary follicles from the oestrous-synchronized control group with that in ACTH-induced or spontaneous follicular cysts, we found a higher expression in the latter. The expression of the TGFB isoforms studied was also altered during folliculogenesis in both the spontaneous and ACTH-induced COD groups. As it has been previously shown that TGFB influences steroidogenesis, ovarian follicular proliferation and apoptosis, an alteration in its expression may contribute to the pathogenesis of this disease.